Progressive emergence of an S153F plus R263K combination of integrase mutations in the proviral DNA of one individual successfully treated with dolutegravir - Pham, H.T.; Alves, B.M.; Yoo, S.; Xiao, M.A.; Leng, J.; Quashie, P.K.; Soares, E.A.; Routy, J.; Soares, M.A.; Mesple`de, T. (Oxford University Press, 2021)
The development of HIV drug resistance against the integrase strand transfer inhibitor dolutegravir is rare. We report here the transient detection, by near full-genome ultradeep sequencing, of minority HIV-1 subtype B variants bearing the S153F and R263K integrase substitutions in the proviral DNA from blood cells of one patient who successfully initiated dolutegravir-based ART, over 24 weeks. Our objective was to study the effects of these substitutions. Strand transfer and DNA-binding activities of recombinant integrase proteins were measured in cell free assays. Cell-based resistance, infectivity and replicative capacities were measured using molecular clones. Structural modelling was performed to understand experimental results. R263K emerged first, followed by the addition of S153F at Week 12. By Week 24, both mutations remained present, but at lower prevalence. We confirmed the coexistence of S153F and R263K on single viral genomes. Combining S153F or S153Y with R263K decreased integration and viral replicative capacity and con ferred high levels of drug resistance against all integrase inhibitors. Alone, S153Y and S153F did little to infectivity or dolutegravir resistance. We identified altered DNA binding as a mechanism of resistance. The patient remained with undetectable viral loads at all timepoints. Drug-resistant minority variants have often been reported under suppressive ART. Our study adds to these observations by unravelling a progression towards higher levels of resistance through a novel pathway despite continuous undetectable viral loads. Poorly replicative HIV drug-resistant minority proviral variants did not compromise viral suppression in one individual treated with dolutegravir.
Research Article